Phytochemical treatments target kynurenine pathway induced oxidative stress - Parasram, K. (Redox Rep, 2017)
Objective: The objective of this paper was to link the phytochemical and metabolic research treating quinolinic acid induced oxidative stress in neurodegenerative disorders. Methods: Quinolinic acid, a metabolite of the kynurenine pathway of tryptophan catabolism, plays a role in the oxidative stress associated with many neurological disorders and is used to simulate disorders such as Parkinson’s disease. Results: In these models, phytochemicals have been shown to reduce striatal lesion size, reduce inflammation and prevent lipid peroxidation caused by quinolinic acid. Conclusion: These results suggest that phenolic compounds, a class of phytochemicals, including flavonoids and diarylheptanoids, should be further studied to develop new treatments for oxidative stress related neurological disorders.